Crosstalk in modern software defined radio for the implementation of frequency modulated continuous wave radar - Faran Awais Butt (Wiley, 2021)
Abstract This study investigates crosstalk and leakage in the Software Defined Radio implementation of Frequency Modulated Continuous Wave (FMCW) radar systems. Empirical measurements of leakage power were conducted during the implementation of FMCW radar using National Instruments Universal Software Radio Peripheral (USRP) boards. Mono‐static and bi‐static/distributed Transmitter‐Receiver configurations are compared for low power micro‐Doppler applications. The impact of crosstalk on the dynamic range of the target is also investigated. The impact of electric noise generated by a windy source on the receiving USRP is also investigated. Furthermore, a simple splitter based approach is proposed to overcome the challenge of synchronisation or recovery of transmitted waveform in distributed configurations.